POLA-POLA UMUM DARI VARIASI BAHASA: KAJIAN SOSIOLINGUISTIK DALAM KONTEKS MASYARAKAT MULTIBAHASA - Ahmad Sururi; Izzudin Musthafa; Ade Nandang (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article aims to examine the general patterns of language variation as a prominent sociolinguistic phenomenon in multilingual societies. Language variation reflects the social, cultural, and identity dynamics of its speakers. The fact that even speakers who share the same mother tongue use different linguistic forms demonstrates how complex and systematic this phenomenon is. Utilizing a descriptive-qualitative approach and a literature review method, this study identifies six main patterns of language variation: (1) speaker-based variation (idiolect, dialect, and sociolect); (2) situational variation (formal and informal registers); (3) geographical variation; (4) age-based variation (chronolect); (5) variation based on communication media; and (6) variation based on group identity. The results of the study show that language variation is not merely a deviation from the norm, but rather an adaptive strategy used by speakers in response to various social contexts. These findings align with the perspective developed by researchers at UIN Sunan Gunung Djati Bandung, who emphasize the role of language as a marker of social and cultural identity.